Prophetic Value in the Folk Story Anthology "East Coast of Central Java" - Nurul Lailatul Aini; Agus Nuryatin; Nas Haryati Setyaningsih (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Literary works certainly have values contained in them, especially prophetic values. Folklore "East Coast of Central Java" was chosen because it is a form of effort to preserve culture in society. The aim of this research is to explain the prophetic value in the Folklore anthology "East Coast of Central Java". This research is research using a pragmatic approach. This pragmatic approach can be seen in the character of each figure in folklore. The method for obtaining data in research uses text research methods. The data acquisition method for this type of text research is based on the data and data sources in the text, in the Folklore anthology "East Coast of Central Java" so that the data is located in the text itself by analyzing the prophetic value contained in the text. The results achieved in this research were the discovery of prophetic studies of humanization, liberation and transcendence. The humanization value found in the Folklore anthology "East Coast of Central Java" consists of aspects of inviting goodness, maintaining brotherhood, and respecting other people; The liberation value found consists of the liberation of the political system; and the transcendence values found in the form of aspects of khauf, raja, tawakkal, gratitude, sincerity and repentance. It is hoped that the results of this research can be used as comparative material and reference material for other researchers who will carry out literary research with similar problems and will be useful for enriching references regarding the study of Indonesian literature, especially in the field of prophetic value.